2010
DOI: 10.1186/1471-2407-10-212
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen regulation of TRPM8 expression in breast cancer cells

Abstract: BackgroundThe calcium-permeable cation channel TRPM8 (melastatin-related transient receptor potential member 8) is over-expressed in several cancers. The present study aimed at investigating the expression, function and potential regulation of TRPM8 channels by ER alpha (estrogen receptor alpha) in breast cancer.MethodsRT-PCR, Western blot, immuno-histochemical, and siRNA techniques were used to investigate TRPM8 expression, its regulation by estrogen receptors, and its expression in breast tissue. To investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 29 publications
1
72
1
1
Order By: Relevance
“…Recently, we also reported the expression and regulation of TRPM8 by estrogens in MCF-7 cells [31]. Two other studies have already shown the expression of TRPC4, TRPC6 and TRPV6 in T47D cells [26] as well as TRPC3 and TRPC6 in MCF-7 and MDA-MB-231 cell lines [32].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Recently, we also reported the expression and regulation of TRPM8 by estrogens in MCF-7 cells [31]. Two other studies have already shown the expression of TRPC4, TRPC6 and TRPV6 in T47D cells [26] as well as TRPC3 and TRPC6 in MCF-7 and MDA-MB-231 cell lines [32].…”
Section: Discussionmentioning
confidence: 82%
“…We have previously demonstrated that TRPC6 and TRPM7 are overexpressed in hBDA at both protein and mRNA levels, and their functional expression was recorded in the MCF-7 cancer cell line and human breast cancer epithelial (hBCE) cells isolated from surgical resection [29,30]. We also reported that TRPM8 expression is regulated by estrogens in breast cancer cells and tissues [31]. Other groups demonstrated that TRPC6 and TRPV6 expression increased in both breast cancer tissues and cell lines, and that both TRPC6 and TRPV6 regulated cell proliferation [26,32].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the subfamilies of TRP channels, TRP channel melastatin 8 (TRPM8) was identified and has been proposed to be the predominant thermoreceptor for cellular and behavioral responses to cold stimuli [7]. Although the aberrant expression of TRPM8 is detected in many tumors [8][9][10][11] and is represented as a key protein in central mechanisms of carcinogenesis, some disagreement of their roles in it was raised in different studies [12].…”
mentioning
confidence: 99%
“…Estrogen in particular has also been shown to induce the expression of TRPV1 channel in rats (Yan et al, 2007). In MCF-7 which is a breast cancer cell line, ERa has been shown to regulate the expression of TRPM8 (Chodon et al, 2010).…”
Section: Steroid-mediated Regulation (Expression) Of Trp Channels (Lomentioning
confidence: 98%